2002
DOI: 10.7547/87507315-92-9-483
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Range-of-Motion Therapy on the Plantar Pressures of Patients with Diabetes Mellitus

Abstract: A randomized controlled study of 19 patients with diabetes mellitus (10 men, 9 women) was undertaken to determine the effects of home exercise therapy on joint mobility and plantar pressures. Of the 19 subjects, 9 subjects performed unsupervised active and passive range-of-motion exercises of the joints in their feet. Each subject was evaluated for joint stiffness and peak plantar pressures at the beginning and conclusion of the study. After only 1 month of therapy, a statistically significant average decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 30 publications
(26 reference statements)
0
89
0
11
Order By: Relevance
“…Few authors have described the subtle, positive effects of foot and ankle exercises in this population, although some studies were not randomized controlled trials [24,25], and others reported on quite short interventions and follow-up periods [26,27]. Therefore, there are still not enough data for conclusions to be arrived at regarding the effectiveness of such interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Few authors have described the subtle, positive effects of foot and ankle exercises in this population, although some studies were not randomized controlled trials [24,25], and others reported on quite short interventions and follow-up periods [26,27]. Therefore, there are still not enough data for conclusions to be arrived at regarding the effectiveness of such interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated promising biomechanical results by incorporating foot-specific exercises in people with DMPN 25 , 64 - 66 . Common elements of foot-specific interventions include toe/forefoot ROM, ankle and subtalar ROM, and intrinsic and extrinsic foot muscle strengthening.…”
Section: Intervention Studies On Dynamic Foot Functionmentioning
confidence: 99%
“…Physical therapy and rehabilitation in diabetic foot of the alphabet with their feet and also practiced passive and active dorsiflexion of the ankles and metatarsophalangeal joints, plantar flexion, active subtalar joint pronation and supination, stretching of the gastrocnemius and soleus muscles. The authors reported that these exercises resulted in a reduction in the joint limitation and foot plantar pressure during walking [60] . In patients with a diabetic foot ulcer, Flahr et al [59] assessed the effects of 10-repetition foot exercises, consisting of the active inversion, eversion, dorsiflexion and plantar flexion of the feet and ankles, practiced twice daily.…”
Section: Electrotherapy Methodsmentioning
confidence: 99%
“…In a study by Goldsmith et al [60] investigating the efficacy of range-of-motion exercises in diabetic foot patients, they asked the patients to draw letters Turan Y et al . Physical therapy and rehabilitation in diabetic foot of the alphabet with their feet and also practiced passive and active dorsiflexion of the ankles and metatarsophalangeal joints, plantar flexion, active subtalar joint pronation and supination, stretching of the gastrocnemius and soleus muscles.…”
Section: Electrotherapy Methodsmentioning
confidence: 99%
See 1 more Smart Citation